Experimental characterization of advanced composite materials - Carlsson, Leif A., 1952-; Adams, Donald F., 1935-; Pipes, R. Byron (CRC Press, 2014)
Over the last three decades, the evolution of techniques for the experimental testing of composite materials has struggled to keep up with the advances and broadening areas of application of the composite materials themselves. In recent years, however, much work has been done to consolidate and better understand the test methods being used. Finally, a consensus regarding the best available methods exists, and definitive recommendations can be made. Experimental Characterization of Advanced Composite Materials provides a succinct, authoritative treatment of the best available methods for determining the mechanical properties, thermal expansion coefficients, and fracture and strength data for composite materials. With an emphasis firmly on practical matters, it presents processing techniques, specimen preparation, analyses of test methods, test procedures, and data reduction schemes. Five chapters covering specific aspects of lamina testing are followed by discussions extending those principles to laminate responses. The treatment concludes by exploring composite durability issues with a detailed examination of defects and fracture mechanics.- Resumé vydavatel
Revised edition of: Experimental characterization of advanced composite materials / Donald F. Adams, Leif A. Carlsson, R. Byron Pipes. 2003. Carlsson's name appears first on earlier editions.
Keywords: kompozitní materiály; lamináty; zkoušení materiálů; composite materials; laminated materials; material testing; elektronické knihy; kolektivní monografie; electronic books; collective monographs